Assessment of cognitive knowledge associated with debriefing in realistic simulation (Research, Society and Development, 2022)
The development of competences by students is closely linked to the use of new teaching modalities, a factor that arouses more interest on the part of students. In this sense, Realistic Simulation (SR) emerges as a form of active methodology that stimulates the teaching-learning process. In this perspective, this study seeks to answer the following research question: what are the ways to assess the cognitive knowledge of medical students during a debriefing in a realistic simulation? With the objective of evaluating the cognitive knowledge of medical students associated with a debriefing in realistic simulation, seeking to highlight the topic addressed. This is a descriptive study with a quantitative approach carried out at the Simulation Center (CSIM) of Centro Universitário Tiradentes-UNIT / AL, located at Hospital Veredas, equipped with high-fidelity mannequins (adult, pregnant and child) for realistic simulation. The Debriefing Assessment Scale associated with Simulation (EADaS) was used as a data collection instrument and 99 students participated in this study, 61 (61.6%) female and 38 (38.4%) male, in the scenarios and Emergency, Obstetrics and Pediatrics. With regard to cognitive aspects, we highlight the structuring of thinking, related to learning, focus on the most important aspects of the simulated experience, deepening of specific knowledge related to simulation and the ability to identify what should be improved in future situations of simulation. The debriefing proved to be an assessment methodology capable of stimulating the development of skills and abilities necessary for the professional practice of medicine.